EPISTEMOLOGI PEMIKIRAN SIR MUHAMMAD IQBAL - Hidayatullah, Syarif (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2018)
This article aims to explore philosophical thoughts of Sir Muhammad Iqbal on several problems which are faced by Moslems. There are three sub topics will be discussed in this article. They are: firstly, characteristic of Iqbal's philosophical thoughts; secondly, roots of Iqbal's philosophical thoughts; and, thirdly, influences of Iqbal's philosophical thoughts toward developments of Western and Islamic philosophy. The material object of this study is Iqbal's philosophical thoughts on several problems of Moslems which will be analyzed by using epistemology as the formal object. This study results three main points. They are: firstly, Iqbal's philosophical thoughts on several problems of Moslems is epistemologically based on Quranic paradigm which is a way to revitalize spirit of intellectualism through three integrated sources of knowledge: sensory perception, reason, and intuition. The Quranic paradigm becomes a thought model of Iqbal especially in reconstructing thoughts of Moslems. Secondly, Iqbal's thoughts are rooted on his belief that ijtihad has a main position in renewal of Islamic thought. Therefore, for him, the Moslems have to open their minds to every good thing, included from the Western, by doing dialogues with Quranic views of Moslems. Thirdly, influence of Iqbal's philosophical thoughts toward developments of Western and Islamic philosophy bases on his success to synthesize Western and Eastern philosophical thoughts with using Quranic paradigm as his epistemological basis.